Enhancing Creative Thinking in Circle Topics through the Realistic Mathematics Learning Approach - Hasibuan, Subriadi; Chu, Cẩm Thơ; Godh, Wessam A. (Interval: Indonesian Journal of Mathematical Education, 2024)
Purpose of the study: This study aims to describe the influence of the Realistic Mathematics learning approach on Students' Creative Thinking Ability in Mathematics in terms of students' mathematics learning achievement, describe the influence of expository learning on students' creative thinking ability and describe the better influence of the 2 learning models applied by looking at the achievements achieved by students. Methodology: This research is a quantitative research and the method used in this research is quasi experiment. The research was conducted at Madrasah Tsanawiyah Al-Ittihadiyah (Mamiyai). The population was all students of class VIII and sampling using cluster random sampling where class VIII-5 as the experimental class and class VIII-1 as the control class. Main Findings: The realistic mathematics learning approach has a good effect on students' creative thinking skills. Expository learning has less effect on students' creative thinking skills. The effect of realistic mathematics learning is better than expository learning. Novelty/Originality of this study: This study provides a new contribution in understanding how a contextual approach can enhance students' creative thinking skills through the exploration of geometric concepts relevant to everyday life.